ORAL CORTICOSTEROID THERAPY FOR SUDDEN SENSORINEURAL HEARING LOSS AND FACTORS AFFECTING PROGNOSIS - Sajid, Tahira; Maisam Ali, Syed; Imran Shah, Mohammad; Hussain, Altaf; zaman , Akhtar; Syeda Rifaat Qamar Naqvi; Sajid, Zara (Journal of Ayub Medical College Abbottabad, 2021)
Background: Sudden sensorineural hearing loss (SSNHL) is considered an otologic emergency globally. Aetiology is unknown in most cases but still the disease is believed to be caused by inflammation of the cochlea; therefore, steroids are considered beneficial due to their anti-inflammatory effect. Methods: This study was conducted on 62 patients of sudden sensorineural hearing loss (SSNHL) in Ayub Medical Complex, Abbottabad. The patients were given prednisolone and their response to the therapy was monitored. Factors like age of the patient, gender, degree of hearing loss and duration of symptoms at initial presentation were recorded and their effect of response of the patient was also noted. Results: The research subjects were 62 patients. Majority of the patients suffered from moderate to moderately severe hearing loss. Age and gender did not influence the response to the treatment. While the patients who presented earlier after the onset of disease and the patients who had milder degree of hearing loss at presentation had a better response to therapy. Conclusion: Oral corticosteroid therapy is a good therapeutic option for the treatment of sudden sensorineural hearing loss (SSHNL). The response to therapy is better in patients with milder hearing loss and those who present early to the otologist for treatment.